1991
DOI: 10.1177/104063879100300312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunoglobulin Light Chains in Canine Extramedullary Plasmacytomas by Thioflavine T and Immunohistochemistry

Abstract: Abstract. Extramedullary plasmacytomas were studied in 29 dogs. The site at which tumors occurred and the age and sex of the dogs were similar to those in previous reports. The skin of the digits, chin, ear, and lip represented the most common (17/29) tumor sites. Males and females were equally represented, and tumors occurred in middle-aged to old dogs (mean age, 9.0 years). A breed predilection was seen in the Cocker Spaniel (n = 7; 24%); Cocker Spaniels represented only 4% (210/4,725) of the submissions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
5
15
1
Order By: Relevance
“…The previous studies revealed that American Cocker Spaniel, English Cocker Spaniel, Airdale Terrier, Kerry Blue Terrier, Scottish Terrier, Yorkshire Terrier, Golden Retriever, Labrador Retriever and mixed breeds are predisposed to EMP (Cangul et al 2002, Gupta et al 2014. The evaluated canine EMPs were seen more often in bitches than in males, in contrary to previous studies (Brunnert andAltman 1991, Cangul et al 2002).…”
Section: Discussioncontrasting
confidence: 53%
“…The previous studies revealed that American Cocker Spaniel, English Cocker Spaniel, Airdale Terrier, Kerry Blue Terrier, Scottish Terrier, Yorkshire Terrier, Golden Retriever, Labrador Retriever and mixed breeds are predisposed to EMP (Cangul et al 2002, Gupta et al 2014. The evaluated canine EMPs were seen more often in bitches than in males, in contrary to previous studies (Brunnert andAltman 1991, Cangul et al 2002).…”
Section: Discussioncontrasting
confidence: 53%
“…In dogs, the examination of plasmacytic infiltrates poses a problem for histopathological diagnosis, because the physiological λ : κ ratio in dogs already appears to indicate light‐chain restriction 17 . Some studies have demonstrated the monoclonal nature of the tumor 18,19 . The positivity to CD138 and λ light chain reveals B‐cell origin.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Immunohistochemical detection of immunoglobulin heavy and light chains has been the standard test for plasma cell differentiation. 1,4,5,13,29,35,38,42,45 However, nonspecific staining may result from adsorption of immunoglobulins to the cell surface, internalization by phagocytes, or binding of immunoglobulins to a variety of cell types via Fc receptors. 46 Although reactivity of CD79a in canine plasmacytoma and B-cell lymphomas is well established, there are large variations in the percentage of cases and number of cells stained with this marker, with up to 80% of plasmacytomas expressing CD79a.…”
Section: Discussionmentioning
confidence: 99%